Information Sources and Factors Influencing Students' Selection of Universiti Malaysia Sarawak. - Songan, Peter; Hong, Kian Sam; Tonga, Noweg; Rahman, Abdul; Tan, Kok Wah (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study investigated the information sources students used to obtain information about University Malaysia Sarawak (UNIMAS) and the factors that contributed to students' selection of UNIMAS as their university of choice. This study employed a cross-sectional survey research design involving 1396 first-year students in UNIMAS. "Ihe two major information sources which the students depended upon for information on UNIMAS were "word of mouth from friends and relatives" and "UNIMAS website". The major factors influencing student choice of UNIMAS were "academic program choice" and "quality of teaching and academics". Academic program choice refers to students' confidence in their ability to meet the demands of the program, good reputation with employers, past graduates' satisfactions with the program, employment rates of past graduates and future prospect of the program. The quality of teaching and academics encompasses the variety of teaching approaches, the use of ICT, quality of academics and academic support services.